2012
DOI: 10.1002/asia.201200557
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Myth of Nascent Hydrogen and its Implications for Biomass Conversions

Abstract: Iron (and to a lesser extent manganese) in the wall of a 316 stainless steel (SS) reactor is responsible for the hydrogenation of cyclohexanone to cyclohexanol when using an aqueous formic acid solution under high temperature and pressure water (HTPW) conditions. However, not only dilute formic acid but also aqueous solutions of several other organic and mineral acids in the presence of iron are active in this reaction covering a range of aldehydes and ketones, even under ambient conditions. The stoichiometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In our previous work, we confirmed that pyruvaldehyde could be hydrogenated under hydrothermal condition in the presence of Fe to produce hydroxyacetone . According to the literature, there are a few possible hydrogenation pathways using zerovalent metal in water (Scheme ). Pathway (i) is initiated by the attack of a highly active hydrogen radical, generated from metallic Fe and a proton, on the carbonyl group.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…In our previous work, we confirmed that pyruvaldehyde could be hydrogenated under hydrothermal condition in the presence of Fe to produce hydroxyacetone . According to the literature, there are a few possible hydrogenation pathways using zerovalent metal in water (Scheme ). Pathway (i) is initiated by the attack of a highly active hydrogen radical, generated from metallic Fe and a proton, on the carbonyl group.…”
Section: Resultssupporting
confidence: 57%
“…Pathway (iii) involves single-electron transfer from metallic Fe to the substrate as the key step. The hydrogen radical in pathway (i) was originally assigned as the so-called “nascent hydrogen”; however, its existence was rejected by several succeeding studies. , Fábos et al proposed pathway (ii) as an alternate explanation for the nascent hydrogen in their work on the mechanism of hydrogenation using metallic Fe and acids . The most general explanation for hydrogenation reactions using zerovalent metals is pathway (iii), which is analogous to the Bouveault–Blanc reduction in which esters are converted into alcohols by metallic Na. , Reduction of aldehydes had also been achieved using Fe, Zn, Mg, Al, and Mn as a reductant. A mechanism has been proposed in which aldehydes adsorbed on the surface of Fe are reduced by single-electron transfer from Fe to form radical intermediates .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fe and Co powder are able to produce nascent H 2 : freshly synthesised H 2 from two hydrogen atoms. The intermediates of this reaction are surface‐bound hydrides [ 57 ] which could, in theory, be directly transferred to NAD + . It is also known that Fe readily produces H 2 from water under mild alkaline conditions [ 58 ].…”
Section: Resultsmentioning
confidence: 99%